Pengaruh Pemupukan Organik Takakura dengan Penambahan EM4 terhadap Pertumbuhan dan Produksi Tanaman Kacang Hijau (Phaseolus radiatus L.) - Z Zuhrufah; Munifatul Izzati; Sri Haryanti (Departemen Biologi, Fakultas Sains dan Matematika Undip, 2015)
Takakura is the research result of scientist Mr. Koji Takakura from Japan. Takakura composting is one of many composting methods not only household composting scale, but also regional scale. This method does not require large tracts of land and its capacity matches with the volume of domestic waste that is disposed by households daily. Household organic waste can be managed easily with this composting method, odorless, does not take a lot of time in the processing and the results are directly utilized. The aim of this research was to know the effect of anorganic (NPK) fertilization and takakura organic fertilization with EM4 addition on growth and production of mung bean. The research was done at Jerukgulung Village, Dempet Area, Demak Regency and Laboratory of Biology and Structure and Function of Plant Faculty of Science and Mathematics Diponegoro University. The design that was used for this research was completely randomized design with single factor, it was the kinds of fertilizer that were used. The data was then analyzed using Analisis of Variance (ANOVA) then continued with Duncan Multiple Test (DMRT) at significant rate 95% to find the real difference. The parameters used were the plant height, number of leaves, number of flower, number of fruit, number of seed, plant fresh weight, fruit fresh weight, seed fresh weight, plant dry weight, fruit dry weight and seed dry weight. The result shows that takakura organic fertilization with EM4 addition influences the plant height, number of leaves, number of flower, number of fruit, plant fresh weight, fruit fresh weight, seed fresh weight and plant dry weight, but doesn’t has any influence to number of seed, fruit dry weight and seed dry weight. Keywords: takakura, anorganic, mung bean (Phaseolus radiatus L.), growth, production.